1996
DOI: 10.1002/pen.10565
|View full text |Cite
|
Sign up to set email alerts
|

Computation of the morphological changes of a polymer blend along a twin‐screw extruder

Abstract: The control of the morphology of an immiscible polymer melt is of vital importance for the mastering of the final properties of the product. As polymer blends are produced using corotating twin‐screw extruders, understanding and modeling the changes experienced by the blend during this process is of great interest. In the present study, starting from Ludovic software, developed for computing flow parameters in the twin‐screw extrusion process, we present a computation of the droplet morphology development, bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0
1

Year Published

1998
1998
2011
2011

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 28 publications
0
43
0
1
Order By: Relevance
“…The preceding results show a significant influence of the mass flow rate on morphology development. Delamare and Vergnes showed that higher feed rates produce 21 lower residence time and are associated with larger particles. In the case of laminar morphology development, the processing window is small.…”
Section: Feed Rate Effect On Morphologymentioning
confidence: 98%
“…The preceding results show a significant influence of the mass flow rate on morphology development. Delamare and Vergnes showed that higher feed rates produce 21 lower residence time and are associated with larger particles. In the case of laminar morphology development, the processing window is small.…”
Section: Feed Rate Effect On Morphologymentioning
confidence: 98%
“…The global computation follows an iterative scheme, since the calculations proceed backward, starting from an arbitrary initial value of the die exit temperature. This software has been successfully used for many applications, such as the study of starch transformation, 24 of blend morphology evolution, 25 or reactive extrusion. 26,27 Figure 4 compares, for different processing conditions, the temperatures measured using the two techniques, that is, flush-mounted PT transducers and a manual thermocouple stuck into the collected melt nut.…”
Section: Softwarementioning
confidence: 99%
“…A better and more readable presentation of such a development was given by Vergnes [154,155] in 1996-1998. They propose and describe forward fluid mechanical and energy balances (Table 6.5).…”
Section: Process Simulation Of Intermeshing Co-rotating Twin-screw Exmentioning
confidence: 99%
“…A more sophisticated development of this model, considering the detailed flows in the kneading disc blocks, was published by Huneault [144,161] of the same group in 1995-96. Delamare and Vergnes [154] have sought to improve the model by attempting to include coalescence.…”
Section: Process Simulation Of Intermeshing Co-rotating Twin-screw Exmentioning
confidence: 99%
See 1 more Smart Citation